Estimating the Error of Fault Location on Overhead Power Lines by Emergency State Parameters Using an Analytical Technique - Aleksandr Kulikov; Pavel Ilyushin; Konstantin Suslov; Sergey Filippov (Energies, 2023)
Fault location on overhead power lines achieved with the highest possible accuracy can reduce the time to locate faults. This contributes to ensuring the stability of power systems, as well as the reliability of power supply to consumers. There are a number of known mathematical techniques based on different physical principles that are used in fault location on overhead power lines and whose errors vary. Fault location on overhead power lines uses techniques based on the estimation of emergency state parameters, which are referred to as distance-to-fault techniques and are widely used. They are employed in digital protection relay terminals and power-line fault locators. Factors that have a significant impact on the error of fault location on overhead power lines by emergency state parameters are design, manufacturing, and operation. The aim of this article is to analyze the existing techniques and to present a new analytical technique for estimating errors of fault location on overhead power lines by using emergency state parameters. The technique developed by the authors makes it possible to properly take into account a set of random factors, including various measurement errors of currents and voltages in the emergency state, which have a significant impact on the fault location on overhead power lines error. The technique allows one to determine more accurately the fault location and the size of the inspection area, which is necessary to reduce the time it takes to carry out emergency recovery operations. The proposed technique can be applied in fault locators and digital protection relay terminals that use both single-end, double- and multi-end sensing of currents and voltages in the emergency state.